(untitled) (The International Journal for Scientific Research, 2023)
This study deals with the explanation and analysis of the basic normative foundations on which the media is built, whether at the level of theory or at the level of field application. It is remarkable that references, despite their importance, may not be given much attention by practitioners of the media process. Rather, more than that, philosophy or philosophical thinking is no longer a starting point or a reference in much scientific research in the literature, humanities, and social sciences. It is noted that the media problems are aggravated through the various media outlets because of the media no longer belonging to a reference and has no foundation or vision center that defines its features and guides its course... The journalist, in fact, is not a technical tool that improves writing news and news reports and takes pictures related to events and facts, as much as he is a man of culture centered with goals, purposes and epistemological references. From this angle, the Journalist needs moral training before getting acquainted with media ethics. Moral is the main guideline for ethics, media low and ethics charters. This study belongs to the analytical qualitative research as an attempt to find out how the ethics that belong to the tree of philosophy are the basis and the center upon which professional ethics are built, including media ethics. The study calls for re-interest in the subject at the academic and professional levels, and this may reduce the idle talk that is spread a lot through the current media.